Clinical incidents in the emergency department: is there an association with emergency nursing shift patterns? A retrospective observational study. Issue 3 (5th August 2022) - Roberts, Kym; Thom, Ogilvie; Hocking, Julia; Bernard, Anne; Doyle, Tammy
Abstract : Introduction: Clinical incident (CI) management within healthcare settings is a crucial component of patient safety and quality improvement. The complex environment in the emergency department (ED) and nursing work schedules are important aspects of human factor ergonomic (HFE) systems that requires closer examination. Nursing shifts are closely related to fatigue, including the late/early shift pattern and night shift. All nursing shifts were examined over a 1-year period when a CI occurred to a patient in the ED to identify if there was an association. Methods: This was a retrospective observational study, conducted and reported using the Strengthening of the Reporting of Observational Studies in Epidemiology statement. All CIs reported in the ED over a 1-year period were reviewed by accessing the CI database, emergency department information system and patient health records. The nursing roster database was accessed to record nursing shifts and were de-identified. Results: A total of n=244 CIs were eligible for inclusion into the study. ED nursing shift analysis included n=1095 nursing shifts. An analysis of early, late and night shifts, including days not worked by the ED nurse was conducted over a 48-hour and 96-hour period. There was no significant relationship identified between the CI and nursing shift patterns. ED length of stay (LOS) was significantly higher for a patient presentation when a CI occurred. Conclusion: This study focused on the HFE system of nursing work schedules and CI events that occurred in the ED. This study found there was no relationship between emergency nursing shift patterns and an increased risk for the occurrence of a CI in the ED. Although a strong link was found between patients experiencing a CI in the ED and an extended LOS. This demonstrates the need for studies to investigate the interrelationships of multiple HFE systems in the ED, including the environment, patient, clinical team and organisational factors.